Modelling of the gas induced fading of organic linings in dry clutches. (December 2015) - Fidlin, Alexander; Bäuerle, Simon; Boy, Felix
Abstract: In this contribution the influence of a phase transition from solid organic material to gas on the contact behaviour in dry clutches is investigated. This phase transition may lead to a decrease in transmissible torque commonly known as fading-effect. This process is modelled by describing the clutch friction surface as a porous medium and calculating the flow and inherent pressure field of a gas formed by a thermally induced decomposition of the organic clutch lining. The basic problem is badly conditioned and therefore reduced by asymptotic development of the governing equations. The simulation results show the capability of the proposed model to predict the influence of the phase transition on the fading-effect. Highlights: AA new model for the effect of outgassing on the dynamical behaviour of a dry clutch. Asymptotic expansion for the pressure field, enabling to overcome numeric problems. Qualitative explanation of both fading and recovery effects. The permeability of the contact layer has been identified as the main parameter.